INSTILLING MORAL VALUES THROUGH THE SONG 'PLEASE AND THANK YOU' IN EARLY CHILDHOOD EDUCATION - Survia, Desty (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2025)
This study explores the moral values embedded in the song “Please and Thank You,” commonly used in early childhood education. Recognizing that early childhood education plays a significant role shaping children’s character and moral development, this study investigates the effectiveness of simple songs in conveying moral messages. The song “Please and Thank You” emphasizes the importance of politeness, manners, and social respect, using the magic words